GAMBARAN PENGETAHUAN REMAJA TENTANG HIV/AIDS DI PUSAT PENGEMBANGAN ANAK ID – 127 KELURAHAN RANOMUT MANADO - Soselisa, Stella M.; Palandeng, Henry M. F.; Andries, Lilian (Jurnal Biomedik : JBM, 2012)
Abstract: AIDS is a collection of symptoms and infections that arise due to the disturbance of the body defence system. There were 24,482 AIDS cases recorded up to the end of March 2011 in 33 provinces in Indonesia. Data from the North Sulawesi Health Department showed that from 1997 until the end of 2010 the distribution of HIV/AIDS continued to increase. This study aimed to find out the understanding about HIV/AIDS in teenagers at the Children’s Development Center ID-127 in Ranomut District, Manado. This was a descriptive study conducted by using a survey method. There were 65 samples of teenagers. The results showed that the teenagers’ understanding about HIV/AIDS was still poor. Their answers about the cause of HIV/AIDS were 27.7% correct; about  the media of infection, 23% correct; about the signs and symptoms, 15.3% correct; about the prevention of HIV/AIDS, 75.3% correct; about the stigma of HIV/AIDS, 63% correct; about using the same utensils, 33.9% correct; and about living in the same house, 49.1% correct. Conclusion: Among the teenagers at the Children’s Development Center ID-127 in Ranomut District, Manado there was poor knowledge about the causes of HIV/AIDS, media of infection, and signs and symptoms; there was good knowledge about prevention of HIV/AIDS; as well as good knowledge about the stigma of HIV/AIDS; but poor knowledge about using the same utensils and living in the same house with HIV/AIDS patients. Keywords: knowledge, teenagers, children development center, HIV/AIDS.   Abstrak: AIDS adalah sekumpulan gejala dan infeksi (sindrom) yang timbul karena terganggunya sistem kekebalan tubuh manusia. Hingga akhir Maret 2011 tercatat 24.482 kasus di 33 provinsi di Indonesia. Data Dinas Kesehatan Sulawesi Utara (Dinkes Sulut) sejak tahun 1997 sampai akhir 2010 memperlihatkan distribusi penderita HIV/AIDS terus mengalami peningkatan. Penelitian ini bertujuan untuk mengetahui pengetahuan mengenai HIV/AIDS dari remaja di Pusat Pengembangan Anak ID-127 kelurahan Ranomut Manado. Penelitian ini bersifat deskriptif dan dilakukan melalui survei. Jumlah sampel yang diperoleh ialah 65 remaja. Hasil penelitian memperlihatkan bahwa pemahaman tentang HIV/AIDS dari para remaja masih kurang. Pengetahuan remaja tentang penyebab HIV/AIDS yang benar 27,7%; tentang media penularan HIV/AIDS yang benar 23%; tentang gejala-gejala HIV/AIDS yang benar 15,3%; dan tentang pencegahan HIV/AIDS yang benar 75,3%. Simpulan: Pada remaja di PPA ID-127 Kelurahan Ranomut Manado, pengetahuan tentang AIDS: masih kurang, mengenai penyebab HIV/AIDS, media penularan, dan gejala-gejala; baik, mengenai pencegahan HIV/AIDS; baik, mengenai stigma HIV/AIDS, dalam hal ini yaitu berjabat tangan dengan pengidap tidak dapat tertular; dan kurang, mengenai tidak dapat tertular bila memakai peralatan yang sama dengan pengidap dan tinggal serumah dengan pengidap. Kata kunci: pengetahuan, remaja, pusat pengembangan anak, HIV/AIDS.